Buckling optimization of blended composite structures using lamination parameters. (September 2020) - Liu, Xiaoyang; Featherston, Carol A.; Kennedy, David
Abstract: In this paper, a new lamination parameter based method is proposed for the layup optimization of built-up composite laminates with ply drop-offs. The optimization process is divided into two stages. In the first stage, the multilevel optimization feature of the exact strip software VICONOPT MLO is extended to use the lamination parameters and laminate thicknesses of each component panel as design variables to minimize the weight of the whole structure subject to buckling and lamination parameter constraints. For the second stage, instead of using the common heuristic optimization methods, a novel dummy layerwise branch and bound (DLBB) method is proposed to search the manufacturable stacking sequences to find those needed to achieve a blended structure based on the use of 0°, 90°, +45° and −45° plies and having lamination parameters equivalent to those determined in the first stage. The DLBB method carries out a logical search to circumvent the stochastic search feature of heuristic methods for the determination of stacking sequences. This two-stage method is an extension of a previous highly efficient two-stage method for a single laminate (Liu et al., 2019) [1]. The effectiveness of the presented method is demonstrated through the optimization of a benchmark wing box. Highlights: Layup optimization of built-up composite laminates with ply drop-off. Multilevel lamination parameter optimization using exact strip buckling analysis. Dummy layerwise branch and bound optimization for manufacturable blended layups. Method demonstrated through blended optimization of a benchmark wing box.